Short-Term Effect of Different Taping Methods on Local Skin Temperature in Healthy Adults - Liu, Kun; Duan, Zhouying; Chen, Lihua; Wen, Zixing; Zhu, Shengqun; Qu, Qiang; Chen, Wenhua; Zhang, Shuxin; Yu, Bo (Frontiers in Physiology, 2020)
Background: There were limited studies on the effect of skin temperature and local blood flow using kinesio tape (KT) adhered to the skin in different taping methods. This study aimed to determine the short-term effect of KT and athletic tape (AT) on skin temperature in the lower back and explore the possible effect of different taping methods (Y-strip and fan-strip taping) on local microcirculation. Material and Methods: Twenty-six healthy participants completed the test-retest reliability measurement of the infrared thermography (IRT), intraclass correlation coefficient (ICC) and standard error of measurement (SEM) were calculated to evaluate the reliability. Then, twenty-one healthy participants received different taping condition randomly for 5 times, including Y-strip of kinesio taping (KY), fan-strip of kinesio taping (Kfan), Y-strip of athletic taping (AY), fan-strip of athletic taping (Afan), and no taping (NT). Above taping methods were applied to the participants’ erector spinae muscles on the same side. Skin temperature of range of interest (ROI) was measured in the taping area through infrared thermography at pre taping and 10 minutes after taping. Additionally, participants completed self-perceived temperature evaluation for different taping methods through visual analogue scaling. One-way repeated-measured analysis of variance was used to compare the temperature difference among different taping methods. Bonferroni test was used for post hoc analysis. Results: There was a good test-retest reliability (ICC=0.82, 95% CI =0.60-0.92; SEM=0.33; MD=0.91) of the infrared thermography. Significant differences were observed in the short-term effect on skin temperature among all different taping methods (p=0.012, F=3.435, ηp2=0.147), post-hoc test showed a higher significantly skin temperature difference in Kfan taping compared to no taping (p=0.026, 95% CI=0.051–1.206); However, no significant differences were observed among self-perceived temperature (p=0.055, F=2.428, ηp2=0.108). Conclusion: This study showed that the fan-strip of KT increased significantly the skin temperature of the waist after taping for 10 minutes. The application of KT may modify the skin temperature of the human body and promote local microcirculation, although it remained unclear for the real application.